Controle da coleção em microfilme Relatórios ministeriais, época do Imperio ([publisher not identified], 1980)
Index to microfilm collection of "Relatórios" of various ministries of the Brazilian federal government during the period of the Empire; filmed as part of a joint project of Plano Nacional de Microfilmagem de Periódicos Brasileiros and Biblioteca Nacional.